AI Crash Course : a Fun and Hands-On Introduction to Reinforcement Learning, Deep Learning, and Artificial Intelligence with Python. - Ponteves, Hadelin de (Packt Publishing, Limited, 2019)
AI legend Hadelin de Ponteves captures his proven AI training approach in a friendly, interactive, and hands-on tutorial book.